Blue sky innovation killer innovations that changed the world of business - Sivapalan Vivekarajah (Dr. Sivalapan Vivekarajah, 2013)
If you've marveled at the success of companies like Apple, IKEA, Salesforce, or AirAsia and dreamt of emulating them but didn't know then you're not alone. What differentiates these great companies from the ordinary ones is innovation and more specifically Blue Sky Innovation. It's innovation with a difference because what made the iPod successful is not the iPod itself but the iTunes music store and what makes IKEA successful is not cheap furniture but innovations from flat packs to store designs and customer services, Swedish meatballs included. This book shows you in a simple but dynamic way that you too can be as innovative as these companies. It shows you why you must think beyond pure product or technology innovation and provides a clear methodology to help you create Blue Sky Innovations that will propel your company onto the next level. The market leaders of today have mastered the art of Blue Sky Innovation and are the leaders in their field. You too can innovate like them and this book shows you how.